Análisis, diseño e implementación de una aplicación web basado en tecnología móvil para geo localización de lugares turísticos de la provincia de los Ríos utilizando la Metodología Extreme Programming en el Año 2014. - Solórzano Farías, Marco Alex (2015)
Currently the tourism sector in the province of Los Rios does not own sources that provide information about tourist attractions that have the province and can be needs at any time or place for tourists. That is why we came up with the initiative to hold the "Analysis, design and implementation of a web application based on mobile technology for geo location of tourist sites in the province of rivers using the methodology extreme programming in 2014" said application Mobile has an administrator profile allows: enter, modify and delete tourist landmarks, from the user profile can be obtained visual information from the geographical location using maps provided by google maps of tourist landmark, also can view information concerning a tourist landmark, the application is also suitable to display distances traveled from a point of interest, the development of this work was based on the use of free software.